2015
DOI: 10.1016/j.bonr.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemic rickets developed after treatment with etidronate disodium in a patient with generalized arterial calcification in infancy

Abstract: Ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) was originally reported as a responsible gene for generalized arterial calcification in infancy (GACI). Though the prognosis of GACI patients is poor because of myocardial infarction and heart failure in relation to medial calcification of the coronary arteries, some patients rescued by bisphosphonate treatment have been reported. Recently, ENPP1 is also reported as responsible for autosomal recessive hypophosphatemic rickets type 2. We show here a boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…β,γ-meATP can be hydrolysed to produce methylene diphosphonate, a bisphosphonate-like compound. Bisphosphonates adhere strongly to a mineralised matrix and have been shown to inhibit both vascular calcification [16,[32][33][34] and bone mineralisation [35,36]. This study found that both methylene diphosphonate and α,β-meADP blocked VSMC calcification at a similar potency to the parent compounds.…”
Section: Discussionmentioning
confidence: 57%
“…β,γ-meATP can be hydrolysed to produce methylene diphosphonate, a bisphosphonate-like compound. Bisphosphonates adhere strongly to a mineralised matrix and have been shown to inhibit both vascular calcification [16,[32][33][34] and bone mineralisation [35,36]. This study found that both methylene diphosphonate and α,β-meADP blocked VSMC calcification at a similar potency to the parent compounds.…”
Section: Discussionmentioning
confidence: 57%
“…The calcifications arise as a consequence of the generalized deficiency of pyrophosphate resulting from biallelic mutations that inactivate the genes encoding either the ectoenzyme ENPP1 (type 1, about 75% of patients), which hydrolyzes ATP to generate pyrophosphate, or ABCC6 (type 2, about 25% of patients), a transmembrane protein that when mutated results in low plasma pyrophosphate (PPi). If affected individuals reach the age of 6 months they are likely to survive and over time may experience spontaneous reversal of vascular calcifications, but severe vascular narrowing may persist along with the development of skeletal deformities described below.…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of the hyperphosphaturia is osteomalacia and rickets, seen in ARHR2. This may indicate an association between ARHR2 and GACI (25). Since arterial calcifications could be lethal in infancy, thesepreviously reported observations encouraged the hypothesis that creating a controlled hypophosphatemia could decrease mortality.…”
Section: Discussionmentioning
confidence: 99%